Pump-free magnetophoresis for improved point-of-care diagnostics - Call, Zachary D., author; Henry, Charles S., advisor; Reynolds, Melissa M., committee member; Dandy, David S., committee member; Snow, Christopher D., committee member (Colorado State University. Libraries, 2022)
Infectious diseases are one of the largest health burdens for low-income countries and claim millions of lives every year. The loss of life in low-income countries is largely due to the lack of access to preventative healthcare and appropriate diagnostic testing. Several health agencies have recognized the need for improved diagnostics to reduce the burden of infectious diseases. The following works described in this thesis are focused on improving the capabilities of point-of-care (POC) testing to improve patient healthcare. Microfluidic devices are a popular approach for diagnostics because they offer reduced assay times, reduced sample volume, and are small (<10 cm). Additionally, microfluidic devices can be used with magnetophoresis to improve sensitivity and specificity. However, traditional microfluidic devices have difficulty translating to the POC because of tedious and expensive fabrication. Microfluidic paper-based analytical devices (µPADs) are a popular alternative to traditional microfluidics due to the natural capillary action through cellulose fibers and simple fabrication. µPADs are portable, low-cost, and do not require external instrumentation, making them ideal for POC settings. However, µPADs often suffer from poor analytical performance resulting in failing to translate to POC testing. In Chapters 2, 3 and 4 of this thesis, I described combining µPADs with magnetophoresis to improve the analytical performance without sacrificing the advantages of µPADs. Coupling magnetophoresis with µPADs is a novel approach and was not reported until the publication of chapter two. Chapter 2 of this thesis describes the first reported example of paper-based magnetophoresis. Magnetophoresis has always needed external pumps to drive flow, however we demonstrate the ability to perform magnetophoresis completely pump-free in a µPAD. We demonstrated the ability to detect E.coli at 105 colony forming units (CFU/mL) with a fluorescent label in a pooled human urine sample. Chapter 3, describes improvements to the device described in chapter two. The limit of detection was improved by three orders of magnitude and calculated at 4.67 x 102 CFU/mL in pooled human urine, which is below detection limits for commercial urinary tract infection tests. Colorimetric detection was used instead of fluorescence detection to eliminate any instrumentation needed and create an easy read-by-eye assay. Additionally, the device design was modified to incorporate a burst valve to generate more consistent laminar flow and simplify user-end steps. We envision this technology to be used a platform for future paper-based devices incorporating magnetophoresis for improved POC devices. In Chapter 4 of this thesis, we describe a new platform for microfluidic magnetophoresis that simplifies user-end steps further through a simple magnet sliding operation. Here we introduce a MagnEtophoresis Slider Assay (MeSA) for sequential binding and washing steps without the need for any external instrumentation. A competitive biotin assay and a sandwich immunoassay are demonstrated to display the functionality of this new platform. The limit of detection was calculated at 1.62 x 103 CFU/mL using colorimetric detection. The MeSA is extremely user-friendly, provides sensitive and rapid results (<15 min), and can be applied to a wide range of applications.